The third mixed problem for the Sonin equation in a half space - Malyts’ka, H. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We consider follwing mixed boundary-value problem: array*20c u’_t (t,R) + xu’_y (t,R) + yu’_z (t,R) = u’’_x^2 (t,R) + f(t,R) in Π _T = { (t,R),0< t T,R = (x,y,z),R E_3 ,0< x} , u(0,R) = u_0 (R),u’_x (t,0,y,z) + β (t)u(t,0,y,z) = g(t,y,z). array A solution of this problem is obtained in the form of a potential.